The late winter diets of barren-ground caribou in North-Central Canada - Thomas, Donald C.; Hervieux, David P. (Rangifer, 1986)
Rumen samples from 104 barren-ground caribou (Rangifer tarandus groenlandicus) collected in March 1980 and 1981 at 18 sites on the winter range in south-central Northwest Territories (NWT) and northern Saskatchewan were examined microscopically for relative occurrence of plant fragments. The composition of plant fragments in the rumens of calves did not differ from that in older caribou. Samples were homogeneous within sites and among them. Therefore we analyzed composite samples for each site and then pooled the data. Terricolous fruticose and foliose lichens averaged 68.5 ± 1.5% (SE) ot tallied fragments at all 18 sites, followed by conifer needles (11.9 ± 1.2%), green leaves of Vactinium spp., Ledum spp., and other shrubs and iorbs (5.6 ± 0.6%), twigs and bark (5.5 ± 0.4%), bryophytes (4.9 ± 0.6%) and 3.6% unidentified. The lichen component consisted of 8.4 ± 1.5% Stereocaulon spp., 46.9 ± 2.6% other fruticose lichens (largely Cladina spp., Cladonia spp., and Cetraria spp.), and 13.2 ± 1.5% foliose lichens (largely Peltigera spp.). A comparison of rumen contents with the average relative abundance of plants found in feeding craters at 13 sites suggests that use of plant species was not always proportionate to their occurrence.